EVALUATION OF BETA CELL FUNCTION IN NEWLY DIAGNOSED TYPE 2 DIABETES MELLITUS IN CLINICAL PRACTICE - Stojanovic, Jelena; Beljić-Živković, Teodora (Medicinski podmladak, 2022)
Dysfunctions underlining type 2 diabetes mellitus (DM2) evolution are insulin resistance and beta-cell secretory insufficiency. Practical but reliable beta-cell function (BCF) testing is still elusive. Methods of BCF measurement include the homeostasis model assessment (HOMA), glucagon stimulation test (GST), oral glucose tolerance tests (OGTT), intravenous glucose tolerance tests (IVGTT), meal tolerance tests (MTT) and the hyperglycemic clamp procedure. Oral tests have the advantage of simpler use and superior approximation of real-life stimulation inclusive for incretin activation effects. The advantage of the test meal over the OGTT incudes a more adequate simulation of nutrients effect on incretin secretion. Therefore, a standardized test meal (STO) would best reflect the spike in insulin secretion after a meal in real life. Conclusion: Standardized test meal, as potent stimulus of C-peptide secretion, is a promising simple and naturalistic alternative to in vivo assess beta-cell function in an affordable outpatient setting, through analysis of C-peptide response in newly diagnosed diabetic patients, as potent stimulus of C-peptide secretion.